Reduced Mannose-Binding Lectin-Associated Serine Protease (MASP)-1 is Associated with Disturbed Coagulation in Septic Shock - Larsen, Julie Brogaard; Laursen, Mathies Appel; Hvas, Christine Lodberg; Larsen, Kim Michael; Thiel, Steffen; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2019)
Background Activation of the complement system is part of the dysregulated immune response in sepsis. The mannose-binding lectin-associated serine proteases (MASP)-1 and -2 activate the lectin pathway of the complement system. Besides, these proteins can activate coagulation in vitro. However, the role of the lectin pathway proteins in the development of sepsis-related disseminated intravascular coagulation (DIC) is only sparsely investigated.Aim This article investigates the association between lectin pathway proteins and coagulation disturbances in septic shock patients.Materials and Methods We included 36 septic shock patients from the intensive care unit, Aarhus University Hospital, Denmark. Blood samples were obtained within 24 hours after admission (day 1), and subsequently on day 2 and day 3. Plasma concentrations of mannose-binding lectin (MBL), H-ficolin, M-ficolin, CL-L1, CL-K1, MASP-1, -2 and -3, MBL-associated proteins of 19 and 44 kDa as well as complement factor C3dg were assessed. Standard coagulation parameters, thrombin generation, thrombin–anti-thrombin (TAT) complex and pro-thrombin fragment 1 + 2 were measured. Sequential Organ Failure Assessment (SOFA) score, DIC score and 30-day mortality were assessed.Results Reduced MASP-1 plasma concentration was associated with DIC score ≥5 (p = 0.02), impaired thrombin generation (p = 0.03) and lower plasma TAT complex levels (p = 0.03). No association was found between lectin pathway proteins and SOFA score or 30-day mortality.Conclusion Reduced MASP-1 concentrations were associated with impaired coagulation in septic shock patients. This indicates that increased MASP-1 activation and consumption is associated with the more severe coagulation disturbances in sepsis and points to a possible role for MASP-1 in sepsis-related DIC.
Keywords: sepsis; disseminated intravascular coagulation; complement pathway, mannose-binding lectin; mannose-binding protein-associated serine proteases